La construcción del hábitat de los sujetos de Andalgalá. ¿En los bordes o más allá del Estado y del capital? (2021)
This article aims to reflect on the extent to which certain actions and strategies implemented by the people of Andalgalá could recreate them as autonomous individuals. This can be affirmed to the extent that such actions would imply another way of building their habitat and assuming health, illness and food. Such strategies can be understood as self-managed experiences located in the margins, rather than beyond the State and capital.